SYNTHESIS AND ANTIMICROBIAL ASSESSMENT OF EFFICACIOUS CARBAZOLE DERIVATIVES - ZUBI SADIQ,; ERUM AKBAR,; NARJIS NAZ, (International Journal of Pharma and Bio Sciences, 2014)
Rooted in invigorating pharmacological applications of carbazole, herein a successful synthesis of some novel and highly potent carbazole derivatives by economically viable means using casual laboratory agents and robust synthetic strategies is detailed. A short linear sequence has been followed to furnish the desired effectual molecules (2-8) having promising anti-microbial activities. All new analogues have been characterized by UV-Vis, FTIR, 1H and 13C NMR, MS and elemental analysis data. The novel chemical moieties have been tested for their bactericidal activity against Methicillin-resistant Staphylococcus aureus, Escherichia coli and for fungicidal property against Aspergillus flavus using agar well diffusion assay showing remarkable antimicrobial potential.